O comércio de madeiras e as restriç\~oes impostas pelos mercados Europeus e Norte-Americanos: Qual a sua efetividade? - Michele Márcia Viana Martins; Marcelo José Braga Nonnenberg (Instituto de Pesquisa Econômica Aplicada (IPEA), 2022)
– Deforestation is considered a highly undesirable practice due to the destruction of local biomes and its effects on global warming. Governments around the world are seeking to adopt measures to control this activity and the international trade in wood and derivatives. Brazil, with the second largest area of forest in the world, also has an arsenal of measures aimed at combating illegal deforestation and the export of these products. However, considering the period 2010 to 2020, it led the international ranking of average net loss of forest areas. The beef and soy export sectors were linked to deforestation in conservation areas and the target of international criticism of the production of commodities. In part, this is expressed in the increase in non-tariff measures issued by the US and the European Union regarding beef and soy. However, it is expected that this concern is also present for wood consumption. It is important that all countries establish strict control over deforestation, and strive in the same direction, regardless of the type of imported product.
Keywords: F18; Q27; 330; wood; deforestation; non-tariff measures; meat; soybeans